Multiple topogenic sequences in bovine opsin. - Audigier, Y (1987)
Bovine opsin, a polytopic integral membrane protein, contains seven transmembrane segments connecting eight hydrophilic domains alternating on each side of the membrane. To localize topogenic sequences that might specify the distinct topology of opsin in the membrane, we constructed various opsin mutants, each containing only one transmembrane segment. Messenger RNAs transcribed from these mutants were translated in a cell-free system supplemented with microsomal membranes. Among six of the seven transmembrane segments of opsin that were analyzed, five were able to function as signal sequences and also expressed stop-transfer sequences of variable strength. By the criteria of extractability at pH 11 and protease sensitivity, the presence of a signal sequence in combination with a "strong" stop-transfer sequence yielded integration into the lipid bilayer of the majority of chains. However, in combination with a "weak" stop-transfer sequence, we observed integration into the lipid bilayer of only some chains, with the others either completely translocated across the membrane or retained in a water-accessible space in the membrane.